2011
DOI: 10.2147/opth.s16355
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of the fixed combination of brinzolamide 1% and timolol 0.5% in daily practice

Abstract: Introduction:The purpose of this study was to document the efficacy and tolerability of the new fixed-combination (FC) brinzolamide 1%/timolol 0.5% as used in daily practice throughout Germany.Methods:An open-label, multicenter, observational study of patients was performed that evaluated the transition from prior medication to brinzolamide/timolol FC for the reduction of intraocular pressure (IOP). Ophthalmologists measured IOP at baseline and 4–6 weeks after transition and assessed their satisfaction with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 8 publications
5
26
1
9
Order By: Relevance
“…The safety and efficacy of BRINZ/TIM-FC and BRINZ + TIM in this study were consistent with those reported in previous studies of these agents as combination therapy and monotherapy in other patient populations 10,11,18,19,21,22,30,31. Similar to the current study, which demonstrated comparable efficacy of BRINZ/TIM-FC and unfixed concomitant BRINZ + TIM, other clinical assessments of fixed-combination therapies have demonstrated that fixed-combination pharmacotherapies containing TIM and dorzolamide, a carbonic anhydrase inhibitor, or latanoprost, a prostaglandin analog, have efficacy similar to that of concomitant treatment with their active components 3235.…”
Section: Discussionsupporting
confidence: 91%
“…The safety and efficacy of BRINZ/TIM-FC and BRINZ + TIM in this study were consistent with those reported in previous studies of these agents as combination therapy and monotherapy in other patient populations 10,11,18,19,21,22,30,31. Similar to the current study, which demonstrated comparable efficacy of BRINZ/TIM-FC and unfixed concomitant BRINZ + TIM, other clinical assessments of fixed-combination therapies have demonstrated that fixed-combination pharmacotherapies containing TIM and dorzolamide, a carbonic anhydrase inhibitor, or latanoprost, a prostaglandin analog, have efficacy similar to that of concomitant treatment with their active components 3235.…”
Section: Discussionsupporting
confidence: 91%
“…One study of more than 10,000 German patients demonstrated the IOP-lowering efficacy of BRINZ/TIM-FC, with IOP reductions from baseline of nearly 4 mmHg; however, this was an open-label clinical trial in a study population that included previously untreated patients 38. A double-masked study compared the IOP-lowering efficacy of TIM monotherapy versus BRINZ/TIM-FC in patients from the United States who were previously untreated or who had undergone a sufficient washout of any prior ocular hypotensives before initiation of the study 23.…”
Section: Discussionmentioning
confidence: 99%
“…BRINZ/TIM-FC has been shown to reduce IOP effectively in patients with open-angle glaucoma and ocular hypertension and to be noninferior to an alternative fixed-combination therapy comprising dorzolamide 2% and timolol 0.5% 1618. In a double-masked, 52-week clinical trial comparing BRINZ/TIM-FC with a fixed combination of dorzolamide/timolol in patients with glaucoma or ocular hypertension, both fixed-combination agents decreased IOP and had safety profiles similar to those observed in the current study 17.…”
Section: Discussionmentioning
confidence: 99%
“…Brinzolamide 1%, a reversible carbonic anhydrase inhibitor, and timolol 0.5%, a β1/β2-blocker, effectively reduce IOP when used individually as topical monotherapy and exhibit increased efficacy when used in combination 16. A fixed combination of brinzolamide 1% and timolol 0.5% (BRINZ/TIM-FC) was demonstrated to be noninferior to a fixed-combination therapy of timolol plus an alternative carbonic anhydrase inhibitor, dorzolamide, and to be preferred over patients’ previous monotherapies and combined therapies 17,18…”
Section: Introductionmentioning
confidence: 99%